Fishery, population dynamics and stock assessment of the spotted seer in gill net fishery at Veraval - Ghosh, Shubhadeep; Pillai, N G K; Dhokia, H K (Indian Journal of Fisheries, 2016)
The fishery and population characteristics of Scomberomorus guttatus (Bloch & Schneider) from Veraval was studied for theperiod 2003 – 2006. The average annual catch was 378 t, forming 14.4% of the total gill net catches at Veraval. The postmonsoonand winter seasons (September to January) were the most productive seasons in terms of catch and catch rate. Thelength–weight relationship showed that growth was isometric for the species. The von Bertalanffy growth equation was:Lt = 61.27 [1 – e - 1.4 (t + 0.0046)] and length attained at the end of 1 and 2 years were 46.3 cm and 57.6 cm respectively. Thegrowth performance index was 3.721 and longevity was 2.138 years. Recruitment pattern was unimodal with peak recruitmentfrom February - July and the length at first capture was 21.1 cm. The natural mortality, fishing mortality and total mortalitywere 1.79, 2.92 and 4.71, respectively and exploitation ratio was 0.62. The maximum sustainable yield was 305 t, which waslower than the average annual catch indicating over-exploitation of the species. The yield per recruit and biomass per recruitwas 198.9 g and 66.9 g respectively. An increase in relative yield to 101.8% would be obtained by decreasing the presentlevel of fishing by 20%.